2013
DOI: 10.3109/01902148.2013.805855
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of plasma 5-HT concentrations during the allergic bronchoconstriction in guinea pigs

Abstract: Several contractile mediators involved in the antigen-induced airway obstruction have been identified, but the role of 5-HT (5-hydroxytryptamine or serotonin) has been scantily investigated. In this work, the potential role of 5-HT in the allergic bronchoconstriction was evaluated through a pharmacological approach and plasma 5-HT measurement in blood samples from the right and left ventricles of anesthetized guinea-pigs. Intravenous 5-HT caused a dose-dependent increase of the lung resistance in anesthetized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus, clinical studies have demonstrated that plasma levels of 5-HT were elevated in a variety of CVD-related pathologies, including hypertension, coronary artery disease, valvular heart disease, atherothrombosis, atherosclerosis, and myocardial infarction (Kaumann and Levy 2006). Likewise, increased 5-HT blood levels were found in patients with asthma (Lechin et al 1996), as well as in animal models of asthma (Segura et al 2010, Arreola-Ramirez et al 2013. Moreover, platelets constitute the major source of 5-HT in blood, and it is known that, in humans, these elements are involved in disorders of the cardiovascular system (Papapanagiotou et al 2016), as well as in asthma (Idzko et al 2015).| Fig.…”
mentioning
confidence: 99%
“…Thus, clinical studies have demonstrated that plasma levels of 5-HT were elevated in a variety of CVD-related pathologies, including hypertension, coronary artery disease, valvular heart disease, atherothrombosis, atherosclerosis, and myocardial infarction (Kaumann and Levy 2006). Likewise, increased 5-HT blood levels were found in patients with asthma (Lechin et al 1996), as well as in animal models of asthma (Segura et al 2010, Arreola-Ramirez et al 2013. Moreover, platelets constitute the major source of 5-HT in blood, and it is known that, in humans, these elements are involved in disorders of the cardiovascular system (Papapanagiotou et al 2016), as well as in asthma (Idzko et al 2015).| Fig.…”
mentioning
confidence: 99%
“…11 While serotonin (5-HT) is best studied as neurotransmitter, 5-HT signaling plays an important role in many organ systems. 28 In the lung it is involved in control of breathing 28 and smooth muscle contractility 29 . Serotonin signaling including HTR4 is involved in human airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NT increases the migration of pulmonary DCs to draining lymph nodes and induces the expression of a Th2 profile in these cells (Müller et al, 2009). Additionally, ASM cells express 5-HT 2A/3/4/7 (Fernandez-Rodriguez et al, 2010;Segura et al, 2010) in MMAA, which mediates bronchoconstriction (Arreola-Ramírez et al, 2013), activating its receptors on parasympathetic ACh-containing neurons, resulting in the release of ACh (Figure 4; Fernandez-Rodriguez et al, 2010). Interestingly, TNF-α up-regulates the contraction mediated by 5-HT via the 5-HT 2A receptor (Adner et al, 2002).…”
Section: Serotoninmentioning
confidence: 99%